2015
DOI: 10.1002/oby.21025
|View full text |Cite
|
Sign up to set email alerts
|

Post‐traumatic stress disorder predicts future weight change in the Millennium Cohort Study

Abstract: Objective: To prospectively examine the association between post-traumatic stress disorder (PTSD) and weight change. Methods: Longitudinal analysis techniques were used to examine data (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008) respectively).Conclusions: PTSD is independently associated with a higher risk of weight gain and loss, the former of which leads to a higher prevalence of overweight and obesity and a higher risk of comorbidities associated with excessive body adiposity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 35 publications
5
24
0
Order By: Relevance
“…Perceived stress and exposure to violence have been associated with a higher prevalence of unhealthy behaviors such as smoking and alcohol use . In addition, negative psychological factors related to violence, such as depression and PTSD, have been linked to tobacco consumption, weight gain, physical inactivity, and adverse cardiac outcomes . In our study we observed a higher prevalence of unhealthy behaviors (smoking history and obesity) in women exposed to violence compared with those not exposed.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Perceived stress and exposure to violence have been associated with a higher prevalence of unhealthy behaviors such as smoking and alcohol use . In addition, negative psychological factors related to violence, such as depression and PTSD, have been linked to tobacco consumption, weight gain, physical inactivity, and adverse cardiac outcomes . In our study we observed a higher prevalence of unhealthy behaviors (smoking history and obesity) in women exposed to violence compared with those not exposed.…”
Section: Discussionsupporting
confidence: 50%
“…31,32 In addition, negative psychological factors related to violence, such as depression and PTSD, have been linked to tobacco consumption, weight gain, physical inactivity, and adverse cardiac outcomes. [33][34][35][36][37][38][39] In our study we observed a higher prevalence of unhealthy behaviors (smoking history and obesity) in women exposed to violence compared with those not exposed. Displayed unhealthy behaviors might reveal another potential mechanism that links exposure to violence and cardiovascular health.…”
Section: Discussionmentioning
confidence: 74%
“…The association between childhood ALEs and obesity is also observed across the lifespan (Richardson, Dietz, & Gordon‐Larsen, ). In military samples, the Millennium Cohort Study (LeardMann et al, ) revealed that a positive PTSD screen predicted ≥10% weight gain at follow‐up. However the PTSD screen does not specify the timing and nature of trauma exposure.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, individuals who endure highly stressful life events often alter their lifestyle choices in a way that would affect cardiovascular health 30. Traumatic life events have been associated with higher chances of smoking, gaining weight, physical inactivity, and elevated CVD risk 10, 11, 31, 32. Pregnancy loss and CVD could also be potentially linked by shared risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Posttraumatic stress disorder along with other stress‐related mental health disorders are associated with incident CVD 8. Abnormal neuroendocrine responses and unhealthy behaviors triggered by highly stressful life events appear to underlie this relation 9, 10, 11…”
Section: Introductionmentioning
confidence: 99%